PRAGMATICS APPROACH IN ENGLISH LANGUAGE TEACHING AT SMA GAJAH MADA 3 PALEMBANG - Eliza, Tiara (International Journal of English Learning and Applied Linguistics (IJELAL), 2023)
In pragmatics, meaning in communication plays a significant part in terms of verbal and nonverbal. It relies upon different settings, relationship among utterers, and social elements. Because the four language skills of reading, writing, listening, and speaking do not occur in isolation in communicative texts or activities, pragmatic is very important in English language teaching. Therefore, developing the language learner's good pragmatic competence should be taken into consideration. It is essential for people who speak the English language, whether native or non-native, to use clear, comprehensible, and educated English so that they can communicate effectively and avoid misunderstandings in social situations. One of the most effective approaches in the learning process, especially learning English at the basic level namely the Pragmatic approach, which is one approach that can be used as a tool to achieve a learning goal especially learning English. Therefore, the aim of this study was how the implementation of pragmatic approach in ELT. The result reveals that the utilizing of pragmatic approach in English language classes require students to play an active role in Learning Activities. Keywords: Pragmatics Approach, English Language Teaching, Implementation of Pragmatic Approach